Correlation between Transabdominal Ultrasound, Prostate Volume and Lower Urinary Tract Symptoms in Men with Benign Prostatic Enlargement - Muhammad Farhan Qureshi, Sasui Memon, Imran Hussain, Aiman Hassan, Muhammad Akhtar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Benign prostatic enlargement (BPE) is a common condition in aging men and frequently presents with lower urinary tract symptoms (LUTS) that significantly affect quality of life. However, the severity of symptoms does not always correlate directly with prostate size. Transabdominal ultrasound (TAUS) provides a non-invasive method for measuring prostate volume, while the International Prostate Symptom Score (IPSS) evaluates symptom severity. Assessing the relationship between prostate volume and IPSS may improve understanding of symptom burden and guide clinical management. Methods: A cross-sectional multicentre study conducted over a period of twelve months. One hundred and fifty men aged 50 years and above presenting with BPE-related LUTS were enrolled after informed consent. Prostate volume was measured via TAUS using the ellipsoid formula. Each patient completed the IPSS and the post-void residual urine (PVR) was recorded. Prostate cancer, previous surgery, active infection, stricture and neurogenic bladder all excluded. Stats: Pearson’s correlation plus one-way ANOVA, p < 0.05 cutoff. Results: A total of 150 patients had the mean age 63.1 year and prostate volume 47.4 mL. mean IPSS was 18.3 showing moderate symptom territory across the board. Our data showed a significant positive correlation between the prostatic volume and IPSS (r = 0.57, p < 0.001). Men above 50mL of PVR were more symptomatic with higher scores and higher residual volume. Weak stream and incomplete emptying dominated the complaint list. Conclusion: TAUS-derived prostate volume correlates significantly with LUTS severity in BPE patients and that supports its routine use in clinical workup. Bladder dysfunction, diabetes, hypertension, all of these feed into symptoms independently. Residual volume is one useful data point. It shouldn’t be the only one driving treatment decisions. Keywords: Benign Prostatic Enlargement, BPE, Cross-Sectional Study, IPSS, Lower Urinary Tract Symptoms, LUTS, Prostate Volume, Transabdominal Ultrasound.